Remote sensing to quantify potential aquifer recharge as a complementary tool for groundwater monitoring - Santarosa, Lucas Vituri [UNESP]; Pinto, Guilherme Vituri Fernandes [UNESP]; Blandón Luengas, Juan Sebastián; Gastmans, Didier [UNESP] (Taylor & Francis, 2024)
Groundwater resources are vital for water security but face threats from overexploitation, contamination, and climate change. This study focuses on the Guarani (GAS) and Bauru (BAS) aquifer systems’ recharge in western São Paulo, Brazil. We enhanced the scalability of the potential recharge (PR) method and assessed recharge using groundwater storage (GWS) data from the Gravity Recovery and Climate Experiment (GRACE). Our findings indicate that while the remote sensing-based PR method aligns with the existing literature, it tends to overestimate recharge. Conversely, the GWS method provides more conservative and reliable estimates. Integrating remote sensing-based methods is a crucial tool for improving recharge estimation and supporting groundwater resource management.
Keywords: aquifer recharge; GRACE; groundwater monitoring; remote sensing; water budget